Audit Quality in State-Owned Enterprise: Audit Costs, Rotation, and Company Size - Yuki; Mustika, Ira Grania; Muhsin (Jurnal Ecoment Global, 2025)
Objective: The purpose of this study is to empirically investigate and contribute to the existing effect of audit fees, auditor rotation, and company size on audit quality in companies listed on IDX during the 2018-2024 period. The research aims to expand the knowledge and insights related to audit quality through rigorous empirical analysis, with a focus on how audit fees, auditor rotation, and company size influence audit outcomes. Design/Methods/Approach: This section encompasses a concise description of the research process employed such as details about the sample, research method, and statistical analysis conducted. Findings: The audit fees significantly negative affect audit quality (Sig. 0.029; Exp(B) = 0.254), contrary to the initial hypothesis. Company size significantly positive effect on audit quality (Sig. 0.047; Exp(B) = 2.801), while auditor rotation does not have a statistically significant impact (Sig. 0.292). Originality/Value: The audit literature highlighting the unique dynamics of State-Owned Enterprises (BUMN) in Indonesia, particularly the relationship between high audit fees and non-technical pressures such as agency conflicts. It also emphasizes the importance of considering the scale of companies and the reputability of KAP in the auditing process. Practical/Policy implication: The findings suggest that regulatory oversight of audit fee setting and consideration of KAP quality in auditor rotation are crucial for ensuring high audit quality. Policymakers and businesses should focus on improving audit practices by addressing the non-technical pressures associated with high audit fees and ensuring the use of reputable KAPs in auditor rotation.